The movement characteristics of English Premiership rugby union players - Cahill, N.; Lamb, K.; Worsfold, P.; Headey, R.; Murray, S. (Journal of Sports Sciences, 2013)
The purpose of this investigation was to quantify the movement characteristics of elite rugby union players during competitive play and identify whether position-related differences exist. Ninety-eight elite players from eight English Premiership Clubs were tracked using global positioning systems (GPS) during 44 competitive matches throughout the 2010/2011 season. Player positions were defined as: (1) Backs or Forwards; (2) Front, Second and Back Rows, Scrum Half, Inside and Outside Backs; (3) 15 individual positions (numbers 1-15). Analysis revealed the game is predominantly played at low speeds with little distance covered `sprinting` by either the Backs (50 ± 76 m) or the Forwards (37 ± 64 m). The Backs travelled greater (P < 0.05) absolute and relative distances than the Forwards. The Scrum Half covered the greatest total distance during a match (7098 ± 778 m) and the Front Row the least (5158 ± 200 m). The Back Row covered the greatest distances at `sprinting` speeds, particularly the number 8 position (77 m). These findings reflect notable differences in the movement characteristics displayed by elite rugby union players in specific positional roles, and reinforce the contemporary view that training programmes for such players ought to be structured with this in mind.